KEDUDUKAN PENYEWA TANAH DALAM PERJANJIAN SEWA MENYEWA TANPA JANGKA WAKTU - Endang Pandamdari; Aldi Pidano (Faculty of Law - Tarumanagara University, 2019)
In carrying out a lease agreement, Article 1570 and 1571 KUHPer regulates the termination of the lease agreement. Although the provisions regarding the existence of an element at a certain time in a lease have been strictly regulated in the KUHPer, in practice there are still many problems in the lease agreement. The problem raised by the author is how the position of the land tenant in the lease agreement without a period of time according to the Supreme Court Decision Number 534 K / PDT / 2016 and how the legal protection of landowners and tenants in the lease agreement rent without time period?. The author examines the problem by using normative legal research methods with the law approach and case approach. The research data shows that the tenant named Maman Kurniawan is not acting in good faith, namely indirectly wanting to take over ownership of other people's property and not returning the goods to others here entering into the main form of illegal acts in the form of illegally possessing objects belonging to another person and the position of Maman Kurniawan in this case is limited to tenants not owners. Then Article 1571 KUHPer is an article that protects the party who rents out in the case of land leasing agreements without a period of time and protection for tenants in the term agreement, namely requesting compensation for land and / or buildings and a certain grace period for tenants to look for other rental places.